The immune microenvironment and expression of PD‐L1, PD‐1, PRAME and MHC I in salivary duct carcinoma. Issue 5 (2nd October 2019) - Xu, Bin; Jungbluth, Achim A; Frosina, Denise; Alzumaili, Bayan; Aleynick, Nathaniel; Slodkowska, Elzbieta; Higgins, Kevin; Ho, Alan; Morris, Luc; Ghossein, Ronald; Katabi, Nora
Abstract : Aims: Salivary duct carcinoma (SDC) is an aggressive salivary malignancy that results in high mortality rates and is often resistant to chemotherapy. Anti‐programmed death‐1 (PD‐1)/programmed death ligand‐1 (PD‐L1) checkpoint inhibitors have led to dramatic improvements in patients with various cancers. Other immunotherapeutic approaches, e.g. cancer vaccines, have shown promising results. Cancer testis antigens, e.g. preferentially expressed antigen in melanoma (PRAME), are regarded as promising vaccine targets because of their tumour‐specific expression pattern. Methods and results: We analysed the immunoexpression of PD‐L1, PD‐1, major histocompatibility complex class I (MHC I) and PRAME in 53 SDCs. The immunoexpression levels of PD‐L1 in tumour cells (TCs) and immune cells (ICs), PD‐1 in ICs, PRAME in TCs and MHC I in TCs were analysed, and were correlated with outcome. PRAME expression was seen in 83% of SDCs. No PRAME staining was present in normal salivary gland tissue. With the three established diagnostic algorithms proposed for head and neck squamous cell carcinoma, the criteria being a combined positive score of ≥1, TC% ≥1%, and TC% ≥25%, 35 (66%), 17 (32%) and three cases (6%), respectively, were deemed to be positive for PD‐L1. PD‐1‐positive ICs were seen in 35 (66%) cases. MHC I down‐regulation was seen in 82% of SDCs. There was a significant correlation among PD‐L1 expression in ICs, PD‐1 expression in ICs, and PRAME expression in TCs. PD‐L1 expression in TCs and lack of PD‐1 expression in ICs were associated with decreased disease‐specific survival in SDC patients. Conclusions: Alterations of the tumour immune microenvironment are common in SDCs, including expression of PD‐1/PD‐L1 and PRAME, which opens the way to potential novel immune therapies, such as cancer vaccination and PD‐1/PD‐L1 blockade, in these tumours.